The Role of Knowledge-Based Economy in Third Generation Universities - Azad Aramaki, Amir; Sedghgooyan, Shahrooz; Lashgari, Narges; Nejad Rasoul, Narges (International Journal of Scientific Research and Management (IJSRM), 2023)
AbstractEntrepreneurial society refers to places where knowledge-based entrepreneurship has emerged as a driving force for economic growth, job creation and competitiveness. In this context, entrepreneurial universities play an important role both as a producer of knowledge and as a publishing institution. In the literature, several studies contributed with relevant findings. Most of these studies show a tendency to use case studies to explain this phenomenon. Paying attention to the role of knowledge in the economy of economic growth is not a new issue, in the way that Adam Smith paid attention to the role of expertise in production and economy in the 18th century. Although the term knowledge-based economy entered the American economic literature in the 1960s, the developments of the 1990s renewed and revived this term, and it has become a very common topic in economic development in recent years. This article uses the library method. Therefore, in this article, according to the importance of the subject, definitions of economy, knowledge and knowledge-based economy are first presented, and then the prerequisites for the establishment of knowledge-based economy and the relationship of third-generation universities in knowledge-based economy are discussed.